WAYS TO DEVELOP HUMAN CAPITAL IN THE CONDITIONS OF INNOVATION ACTIVITY AND DIGITAL ECONOMY - Asatullayev Khurshid Sunatullayevich; Matyoqubova Muxayyo Baxtiyor kizi (Western European Studies, 2024)
This article provides scientifically based proposals and practical recommendations for the development of human capital through involvement in the innovation sector, large-scale digitization of the economy, strengthening the integration of Science, Education and business.
Keywords: Innovation activity; digital economy; human capital